0
$\begingroup$

The problem: Now find a polynomial function $f$ of degree $n - 1$ such that $f(x_i) = a_i$, where $a, \ldots, a_n$ are given numbers.

I found that this question had been asked before, but I did not understand the solution.

Moving on to the actual problem: we are asked to use the formula derived in the previous problem, which is: $$f_i(x) = \prod^n_{j = 1, j \neq i}\frac{x - x_j}{x_i - x_j}.$$ This function is equal to $0$ for all $x_j$ if $j \neq i$, and equal to $1$ at $x_i$. Note that $x_j$ and $x_i$ come from the list of distinct numbers $x_1, \ldots, x_n$.


My thinking as to the solution is that we simply need to multiply $f_i(x)$ by $a_i$, giving us $$f(x) = a_i \cdot \prod^n_{j = 1, j \neq i}\frac{x - x_j}{x_i - x_j}.$$ Then when we plug in $x_i$ we would have $$f(x_i) = a_i \cdot \prod^n_{j = 1, j \neq i}\frac{x_i - x_j}{x_i - x_j} = a_i.$$

However, in the answer key, solution is $$f(x) = \sum^n_{i = 1} a_i \cdot \prod^n_{j = 1, j \neq i}\frac{x_i - x_j}{x_i - x_j}.$$ This seems like it must be false, as substituting in $x_i$ gives us $$f(x_i) = \sum^n_{i = 1} \cdot \prod^n_{j = 1, j \neq i}\frac{x_i - x_j}{x_i - x_j} = \sum^n_{i = 1} a_i.$$ It looks to me like $\sum^n_{i = 1} a_i$ only equals $a_i$ if $n = 1$. As a result, I'm very confused as to how this answer could be correct. Any clarification would be appreciated.

$\endgroup$
  • $\begingroup$ The product is within the sum - so you have a different product for each of the terms of the sum. When you plug in $x_i$ the various products are zero except for the $i^{th}$ one and this picks out the value $a_i$ for $f(x_i)$. In your formulation $f(x_j)=0$ for $j\neq i$. $\endgroup$ – Mark Bennet May 20 at 21:58
2
$\begingroup$

Since $\prod_{j=1,j\neq i}^n\frac{x-x_j}{x_i-x_j}$ maps $x_i$ into $1$ and every $x_j$ (with $j\neq i$) into $0$, then clearly$$\sum_{i=1}^na_i\prod_{j=1,j\neq i}^n\frac{x-x_j}{x_i-x_j}\tag1$$is what you're after. Pick some $i\in\{1,2,\ldots,n\}$. Then $(1)$ maps $x_i$ into$$a_1\times0+a_2\times0+\cdots+a_{i-1}\times0+a_i\times1+a_{i+1}\times0+\cdots+a_n\times0=a_i.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.